Renal insufficiency mimicking glutaric acidemia type 1 on newborn screening. Issue 1 (14th December 2017) - Matsumoto, Masaaki; Awano, Hiroyuki; Bo, Ryosuke; Nagai, Masashi; Tomioka, Kazumi; Nishiyama, Masahiro; Ninchouji, Takeshi; Nagase, Hiroaki; Yagi, Mariko; Morioka, Ichiro; Hasegawa, Yuki; Takeshima, Yasuhiro; et al.
Abstract: Background: Glutaryl carnitine (C5DC) in dried blood spots is used as a biomarker for glutaric aciduria type 1 (GA‐1) screening. C5DC, however, is the only screening marker for this condition, and various pathological conditions may interfere with C5DC metabolism. Recently, C5DC elevation has been reported in cases of renal insufficiency. Method: Five patients who were positive for GA‐1 on newborn screening with tandem mass spectrometry between September 2012 and March 2015 at Kobe University Hospital were enrolled in this study. Results: GA‐1 was not confirmed on urinary organic acids analysis in any of the patients. C5DC decreased immediately in four patients, but one patient, who had high C5DC for at least 4 months, was diagnosed with bilateral renal hypoplasia. Conclusion: In the case of persistently elevated C5DC, renal insufficiency should be considered as a differential diagnosis.